2017
DOI: 10.1093/icvts/ivx033
|View full text |Cite
|
Sign up to set email alerts
|

Flow-dynamics assessment of mitral-valve surgery by intraoperative vector flow mapping

Abstract: Mitral valve replacement alters the intraventricular vortex pattern and increases flow energy loss. A small mitral-septal angle is a risk factor for abnormal vortex patterns after mitral valve repair surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…8À11 After mitral valve replacement, the vorticial flow patterns are disrupted and energy loss increases. 8,12 How the physiologic flow patterns are disrupted depends on both the type of mitral prosthesis used and the prosthetic valve orientation. 13À15 Mitral repairs in contrast to prosthetic mitral valves maintain a closer to physiologic vorticial flow pattern in the left ventricle and are associated with decreased energy loss.…”
Section: Left Ventricular Vortex Formationmentioning
confidence: 99%
“…8À11 After mitral valve replacement, the vorticial flow patterns are disrupted and energy loss increases. 8,12 How the physiologic flow patterns are disrupted depends on both the type of mitral prosthesis used and the prosthetic valve orientation. 13À15 Mitral repairs in contrast to prosthetic mitral valves maintain a closer to physiologic vorticial flow pattern in the left ventricle and are associated with decreased energy loss.…”
Section: Left Ventricular Vortex Formationmentioning
confidence: 99%
“…Modern imaging modalities later confirmed vortical flow patterns to be a common feature in the heart, where vortices appear during diastole, associated with a smooth redirection of flow from the inflow to the outflow tract. It is argued that these specific flow patterns allow for kinetic energy preservation for subsequent ejections and are disturbed in patients with myocardial infarction, dilated cardiomyopathy or heart failure as well as after surgical valve interventions . It has been shown that the contribution of the diastolic vortex ring to diastolic left ventricular filling is significantly decreased in abnormal ventricles .…”
Section: Introductionmentioning
confidence: 99%
“…It is argued that these specific flow patterns allow for kinetic energy preservation for subsequent ejections 5,6 and are disturbed in patients with myocardial infarction, dilated cardiomyopathy or heart failure 7,8 as well as after surgical valve interventions. 9 It has been shown that the contribution of the diastolic vortex ring to diastolic left ventricular filling is significantly decreased in abnormal ventricles. 10 Based on their findings at resting heart rates, it was hypothesized that the vortex contribution to ventricular filling is increased during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…EL elevates at sites where velocity vectors change the magnitude and direction. Such as, EL is probably to increase within turbulent flow, like at a point after mitral valve replacement . The endocardial border was manually traced at the maximal volumes of LA, and then automatically obtained for remaining frames.…”
Section: Methodsmentioning
confidence: 99%
“…Such as, EL is probably to increase within turbulent flow, like at a point after mitral valve replacement. 13 The endocardial border was manually traced at the maximal volumes of LA, and then automatically obtained for remaining frames. After automatically tracing, EL (measurement in N/(m·s)) was assessed at every frame.…”
Section: Analysis Of Energy Lossmentioning
confidence: 99%